(untitled) (Estudios humanísticos. Geografía, historia y arte, 1993)
The convent of La Concepción at Villafranca del Bierzo (León), preserves a decoration of «esgrafiados» in the stairs of the convent. It’s a decoration of the 16th Century , in which appears an iconographic program.